ESTIMASI POPULASI TOKEK RUMAH, GEKKO GECKO (LINNAEUS, 1758) DI KAKI GUNUNG KARANG, KABUPATEN PANDEGLANG, PROVINSI BANTEN, JAWA BAGIAN BARAT - Kurniati, Hellen (Perhimpunan Biologi Indonesia, 2019)
ABSTRACTOn CoP 18 which will be held in Sri Lanka in 2019, house gecko was proposed to be uplisted up listed from the non-appendix status of CITES to be included the list of CITES appendix II on the reasons that the hunting of the reptile was very large and uncontrolled. In order to anticipate the up listing of house gecko status, LIPI as a Scientific Authority in Indonesia recommended quota for house gecko in 2019 to be 1,800,000 individuals. To see that such a quota does not have a negative impact on the population of house gecko in the wild, a survey was conducted by using the close questioner system method by visiting housing in a village; where in this survey the villages were located at the foot hill of Gunung Karang, Pandeglang Regency, Banten Province. The survey was conducted on March 18 to April 1, 2019. The total number of villages visited was 8 villages which were divided into three sub-districts. The total area surveyed in 8 villages was around 94.5 hectares. The total number of houses visited was 740 houses; the total number of houses that contained the house gecko was 211 houses. The total number of house gecko by interviewed was 260 individuals, while the total number of house geckos by observed was 88 individuals. The survey results obtained an average population density of house gecko by interviewing eight villages was 3.66 individuals/hectares, while the observation results were 1.15 individuals/hectares. The approach to the average population density of houses gecko by interviewing with the results of 3.66 individuals/hectares was assumed to be the density that was close to the logical number. Extrapolating the density of house geckos in Pandeglang Regency which covers an area of 229,071 hectares excluded paddy field area was considered to be inhabited by house gecko, so the extrapolation of the number of house geckos in Pandeglang Regency is around 838,399.86 individuals. Keywords: Gekko gecko, house gecko, Java, population